Deep and continuous sedation until death in the French overseas departments - Sophie Pennec; Hélèna Briand; Vincent Guion; Adrien Evin (PLoS ONE, 2025)
Background Continuous deep sedation until death (CDSUD) has been a legally recognised end-of-life right in France since 2016. Data on implementation remain limited, particularly in the French overseas departments, which share the same legal framework as mainland France but present a more rapidly ageing population. This study describes the characteristics of patients who received CDSUD, the profiles of the physicians involved, the modes of implementation, and the emotional impact of CDSUD on physicians. Method We conducted a retrospective, questionnaire-based survey among physicians who certified deaths in four French overseas departments. The study population comprised a random sample of adult deaths between March 2020 and February 2021. CDSUD cases were identified through a multidisciplinary review process. Findings Of 1,082 informed non-sudden deaths, CDSUD was implemented in 128 cases (11.8%), mainly in hospitals, among younger patients without cognitive impairment. midazolam or benzodiazepine were used in 78.8% of cases, often combined with morphine. A colleague was consulted in 80% of cases, though formal collegiality was not systematic. Physicians mainly aimed to relieve unbearable suffering. They acknowledged possible hastening of death, although this was rarely their intention. The emotional impact on physicians was similar, whether or not CDSUD was performed. Interpretation This first population-based study of CDSUD in the French overseas departments highlights the need to improve access to this practice, particularly for older adults and those receiving end-of-life care at home. Further prospective and qualitative research is needed.